Predicting outcomes of investments in maintenance and repair of federal facilities (National Academies Press, 2012)
"The deteriorating condition of federal facilities poses economic, safety, operational, and environmental risks to the federal government, to the achievement of the missions of federal agencies, and to the achievement of public policy goals. Primary factors underlying this deterioration are the age of federal facilities--about half are at least 50 years old--and decades of inadequate investment for their maintenance and repair. These issues are not new and there are no quick fixes. However, the current operating environment provides both the impetus and the opportunity to place investments in federal facilities' maintenance and repair on a new, more sustainable course for the 21st Century. Despite the magnitude of investments, funding for the maintenance and repair of federal facilities has been inadequate for many years, and myriad projects have been deferred. Predicting Outcomes of Investments in Maintenance and Repair of Federal Facilities identifies processes and practices for transforming the current portfolio of federal facilities into one that is more economically, physically, and environmentally sustainable. This report addresses ways to predict or quantify the outcomes that can be expected from a given level of maintenance and repair investments in federal facilities or facilities' systems, and what strategies, measures, and data should be in place to determine the actual outcomes of facilities maintenance and repair investments."--Publisher's description.